Sensitivity of human pleural mesothelioma to oncolytic measles virus depends on defects of the type I interferon response - Achard, Carole (Oncotarget, 2015)
Attenuated measles virus (MV) is currently being evaluated as an oncolytic virus in clinical trials and could represent a new therapeutic approach for malignant pleural mesothelioma (MPM). Herein, we screened the sensitivity to MV infection and replication of twenty-two human MPM cell lines and some healthy primary cells. We show that MV replicates in fifteen of the twenty-two MPM cell lines. Despite overexpression of CD46 by a majority of MPM cell lines compared to healthy cells, we found that the sensitivity to MV replication did not correlate with this overexpression. We then evaluated the antiviral type I interferon (IFN) responses of MPM cell lines and healthy cells. We found that healthy cells and the seven insensitive MPM cell lines developed a type I IFN response in presence of the virus, thereby inhibiting replication. In contrast, eleven of the fifteen sensitive MPM cell lines were unable to develop a complete type I IFN response in presence of MV. Finally, we show that addition of type I IFN onto MV sensitive tumor cell lines inhibits replication. These results demonstrate that defects in type I IFN response are frequent in MPM and that MV takes advantage of these defects to exert oncolytic activity.